2021
DOI: 10.7554/elife.54782
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of Wnt7b expression by the cis-acting long noncoding RNA Lnc-Rewind in muscle stem cells

Abstract: Skeletal muscle possesses an outstanding capacity to regenerate upon injury due to the adult muscle stem cell (MuSC) activity. This ability requires the proper balance between MuSC expansion and differentiation, which is critical for muscle homeostasis and contributes, if deregulated, to muscle diseases. Here, we functionally characterize a novel chromatin-associated long noncoding RNA (lncRNA), Lnc-Rewind, which is expressed in murine MuSCs and conserved in human. We find that, in mouse, Lnc-Rewind acts as an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…This result was also mirrored in vivo in cardiotoxin-induced mice in addition to a reduced number of newly formed myofibers [170]. A further example is Lnc-Rewind (Repressor of wnt induction), a chromatin-associated lncRNA previously identified by transcriptomic analysis [187] and recently shown to act as an epigenetic regulator of satellite cells proliferation and expansion [172]. Mechanistically, Lnc-Rewind directly interacts with the methyltransferase G9a to mediate the repression of its neighboring gene, Wnt7b, the expression of which is important for satellite cells' differentiation (Figure 3C).…”
Section: Nuclear Ncrnasmentioning
confidence: 78%
See 2 more Smart Citations
“…This result was also mirrored in vivo in cardiotoxin-induced mice in addition to a reduced number of newly formed myofibers [170]. A further example is Lnc-Rewind (Repressor of wnt induction), a chromatin-associated lncRNA previously identified by transcriptomic analysis [187] and recently shown to act as an epigenetic regulator of satellite cells proliferation and expansion [172]. Mechanistically, Lnc-Rewind directly interacts with the methyltransferase G9a to mediate the repression of its neighboring gene, Wnt7b, the expression of which is important for satellite cells' differentiation (Figure 3C).…”
Section: Nuclear Ncrnasmentioning
confidence: 78%
“…Mechanistically, Lnc-Rewind directly interacts with the methyltransferase G9a to mediate the repression of its neighboring gene, Wnt7b, the expression of which is important for satellite cells' differentiation (Figure 3C). Consistently, the depletion of Lnc-Rewind in MuSC-derived myoblasts leads to Wnt7b de-repression and to the aberrant expansion and activation of satellite pools on single myofibers [172]. Finally, we cannot fail to mention H19, one of the earliest lncRNAs to be identified and shown to exert diverse functions in varying types of cells, including satellite, cardiac, and skeletal muscle cells [188,189].…”
Section: Nuclear Ncrnasmentioning
confidence: 88%
See 1 more Smart Citation
“…It interacts with G9a histone lysine methyl transferase to help recruit repressive histone marker H3K9me2 and repress the expression of Wnt7b. LncRewind depletion leads to MuSC differentiation defects (Cipriano et al 2021 ).…”
Section: Transcription and Epigenetic Regulation Of Musc Fate Transitionmentioning
confidence: 99%
“…Numerous studies have indicated that lncRNAs exert either positive or negative effects to regulate the expression of neighboring protein-coding genes [20,21]. Therefore, we extracted the information related to the location of differential lncRNAs from the transcription file and porcine genome database (http://genome-asia.ucsc.edu) and selected mRNAs located within 10 kb upstream or downstream of these lncRNAs.…”
Section: Potential Cis-regulatory Mechanisms Between Porcine Delncrna...mentioning
confidence: 99%